Long polar fimbriae participates in the induction of neutrophils transepithelial migration across intestinal cells infected with enterohemorrhagic E. coli O157:H7 - Vergara, Alejandra F.; Vidal, Roberto M.; Torres, Alfredo G.; Farfan, Mauricio J. (Frontiers in Cellular and Infection Microbiology, 2015)
Enterohemorrhagic Escherichia coli (EHEC) strains are causative agents of diarrhea and hemorrhagic colitis, both diseases associated with intestinal inflammation and cell damage. Several studies have correlated EHEC virulence factors to high levels of intestinal pro-inflammatory cytokines and we have previously described that the Long polar fimbriae (Lpf) is involved in the secretion of interleukin-8 (IL-8) and up-regulation of genes belonging to the NF-κB pathway using non-polarized epithelial intestinal T84 cells. In the current study, we evaluated the two EHEC O157 Lpf fimbriae (Lpf1 and Lpf2) for their ability to induce intestinal secretion of IL-8 and the activation of IL8, CCL20 and ICAM1 genes on polarized T84 cells. We also determined the participation of Lpf1 and Lpf2 in transepithelial migration of polymorphonuclear neutrophils (PMNs). Polarized T84 cells infected with EHEC revealed that both, Lpf1 and Lpf2, were required for the secretion of IL-8 and the induction of IL8, CCL20 and ICAM1 genes. Both fimbriae also played a role in the migration of PMNs trough the intestinal cells monolayer. Overall, the present work further demonstrated that the fimbriae Lpf1 and Lpf2 are important bacterial virulence factors that might be involved in the inflammatory responses associated with EHEC infections.